William C. Bullitt and the Soviet Union - Farnsworth, Beatrice (Indiana University Press, 1967)
This account of the stormy career of a controversial figure in United States diplomacy draws upon all available sources, including the previously inaccessible Bullitt papers at Yale University. It focuses principally on Bullitt's contribution to Russian-American policy during the WIlson administration and as adviser on Soviet affairs to Franklin Roosevelt. These revealing chapters in recent diplomatic history show how Bullitt's contact with the harsh facts of international politics gradually extinguished his enthusiastic hope for a new world to follow World War I.